2022
DOI: 10.3311/ppci.21360
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric Investigation of the Influence of Knots on the Flexural Behavior of Timber Beams

Abstract: The presence of knots significantly influences the mechanical behavior of timber. This research presents a parametric finite element analysis of the effect of knot characteristics on the flexural capacity of timber beams. Parameters include knot radius, longitudinal and vertical positions, length, and diving angle. The generation of the FE model is based on a technique developed in a previous research stage. The validation of the model is done via bending tests on a set of beams as well as a number of independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Therefore, it is necessary to study and experiment to identify the factors that affect its strength. In addition to the grade of sawn timber, several studies have reported the influence of factors on strength, such as drying temperature, density, knots, and slope of grain (Gerhards 1983;Nagai et al 2011;Saad and Lengyel 2023). Typical types of defects in wood that cause failure of structural lumber mainly include ring failure, checks, wane, knots, and grain angle.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to study and experiment to identify the factors that affect its strength. In addition to the grade of sawn timber, several studies have reported the influence of factors on strength, such as drying temperature, density, knots, and slope of grain (Gerhards 1983;Nagai et al 2011;Saad and Lengyel 2023). Typical types of defects in wood that cause failure of structural lumber mainly include ring failure, checks, wane, knots, and grain angle.…”
Section: Introductionmentioning
confidence: 99%
“…Their research is based on the analysis of an elastic and plastic orthotropic material (biaxial anisotropic), and the conclusion is that Hill's criterion can be applied for modelling of those materials. The same authors show that material model can be successfully used for modelling of timber with discontinuities -knots [8]. The main disadvantage of the continuum models is the lack of material models that are ready to use in contemporary engineering software.…”
Section: Introductionmentioning
confidence: 99%